2004
DOI: 10.1007/s00213-003-1612-x
|View full text |Cite
|
Sign up to set email alerts
|

Influences of ethanol ingestion on olfactory function in humans

Abstract: Alcohol ingestion markedly and selectively alters olfactory sensitivity to ethanol, perhaps via habituation processes, and may subtly influence some measures of odor discrimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 35 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…For instance, Engen [32] have reported that subjects with ethanol-intoxicated blood levels tend to show enhanced performance for odor detection of guaiacol. However, in another study conducted by Patel et al [33], acute alcohol ingestion markedly decreased olfactory threshold sensitivity to ethanol, but not to phenyl ethyl alcohol. Thus, the selection of odorant and degree of olfactory dysfunction in subjects should be considered in future studies.…”
Section: Discussionmentioning
confidence: 84%
“…For instance, Engen [32] have reported that subjects with ethanol-intoxicated blood levels tend to show enhanced performance for odor detection of guaiacol. However, in another study conducted by Patel et al [33], acute alcohol ingestion markedly decreased olfactory threshold sensitivity to ethanol, but not to phenyl ethyl alcohol. Thus, the selection of odorant and degree of olfactory dysfunction in subjects should be considered in future studies.…”
Section: Discussionmentioning
confidence: 84%
“…This, however, was a between-subjects design, susceptible to non-alcohol related group differences. In contrast, other studies using within subject designs reported either declined [30][31][32], or unchanged [31] olfactory performance following alcohol consumption. Here we set out to test the hypothesis that alcohol may improve olfactory performance in three separate experimental designs.…”
Section: Introductionmentioning
confidence: 72%
“…Furthermore, demographic factors such as gender and age, or individual habits like alcohol consumption or cigarette smoking are significantly related to olfactory function (Doty 2003;Duncan and Smith 1995;Patel et al 2004;Schiffman 1997), but their relevance was overlooked in some epidemiological studies in workers. Valid information on interfering factors and on reference values for the not exposed group is also necessary.…”
Section: Discussionmentioning
confidence: 98%